2005
DOI: 10.4315/0362-028x-68.5.966
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Viable Mycobacterium avium subsp. paratuberculosis in Retail Pasteurized Whole Milk by Two Culture Methods and PCR

Abstract: Cattle with Johne's disease can shed live Mycobacterium avium subsp. paratuberculosis (MAP) in their milk, and MAP can survive under simulated commercial pasteurization conditions. In several studies conducted in the United Kingdom and Canada, MAP DNA has been detected in retail pasteurized milk samples; however, in one study in the United Kingdom viable MAP was identified in commercially pasteurized milk. A double-blind study involving two laboratories was undertaken to evaluate retail pasteurized whole milk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
135
1
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(145 citation statements)
references
References 30 publications
4
135
1
5
Order By: Relevance
“…Confirmed MAP isolates were cultured from 1.8% of the commercially pasteurized milk samples in the U.K. (Grant et al, 2002). Similar data were published from the U.S.A. (Ellingson et al, 2005). In the U.K. study the 10 culture-positive pasteurized milk samples were from just 8 (3.3%) of the 241 dairy processing establishments that participated in the survey (Grant et al, 2002).…”
supporting
confidence: 62%
“…Confirmed MAP isolates were cultured from 1.8% of the commercially pasteurized milk samples in the U.K. (Grant et al, 2002). Similar data were published from the U.S.A. (Ellingson et al, 2005). In the U.K. study the 10 culture-positive pasteurized milk samples were from just 8 (3.3%) of the 241 dairy processing establishments that participated in the survey (Grant et al, 2002).…”
supporting
confidence: 62%
“…Our estimated MAP concentration in raw milk was 10 4 CFU/mL in the worst case; therefore heat inactivation should be effective. Still, MAP isolation in milk sampled at retail stores has been reported (Ellingson et al, 2005;Stephan et al, 2007). It has recently been reported that spore-forming MAP may survive heat treatments of 70°C (Lamont et al, 2012), which could explain the occasional MAP survival after heat treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Most milk produced on cattle farms in dairy-producing countries is pasteurized, which may reduce MAP in milk by 4-7 log 10 (Cerf et al, 2007). However, MAP bacteria and DNA have been found in dairy products in retail stores, indicating survival of MAP during the processing (Ellingson et al, 2005;Stephan et al, 2007). The increasing implications of the role of MAP in Crohn's disease suggest that minimizing contamination of milk at the farm level may be advisable.…”
Section: Introductionmentioning
confidence: 99%
“…2,[4][5][6][7][8][9][10][11][12] As Johne disease has become an increasingly worldwide problem, due in part to the absence of preventive vaccine/drug or curative treatments, 13 including the partially protective, MAP subunit vaccine, 14 awareness as to what role, if any, animals play in the transmission of MAP to humans is being raised. [15][16][17][18][19][20][21] This concern arises from the apparent specific association of MAP with Crohn disease, even though a role (etiology agent?) remains to be established.…”
Section: Introductionmentioning
confidence: 99%